Melatonin inhibits MUC5AC production via suppression of MAPK signaling in human airway epithelial cells. Issue 4 (28th March 2014) - Shin, In‐Sik; Park, Ji‐Won; Shin, Na‐Rae; Jeon, Chan‐Mi; Kwon, Ok‐Kyoung; Lee, Mee‐Young; Kim, Hui‐Seong; Kim, Jong‐Choon; Oh, Sei‐Ryang; Ahn, Kyung‐Seop
Abstract Mucus acts as a primary defense system in the airway against various stimuli. However, excess mucus production causes a reduction in lung function via limitation of the airflow in the airway of patients suffering from asthma or chronic obstructive pulmonary disease (COPD). In this study, we evaluated the effects of melatonin on the production of MUC5AC, a major constituent of the mucin that is secreted from the airway, using epidermal growth factor (EGF)‐stimulated NCI‐H292 cells, a human mucoepidermoid carcinoma cell line, and an ovalbumin (OVA)‐induced asthma murine model. Melatonin treatment significantly reduced the mRNA and protein levels of MUC5AC and reduced interleukin (IL)‐6 production in EGF‐stimulated H292 cells. Melatonin markedly decreased the phosphorylation of MAPKs, including ERK1/2, JNK, and p‐38, induced by EGF stimulation. These findings were consistent with the results using MAPK inhibitors. Particularly, co‐treatment with melatonin and a MAPK inhibitor more effectively suppressed MAPK phosphorylation than treatment with a MAPK inhibitor alone, which resulted in a reduction in MUC5AC expression. In the asthma murine model, melatonin‐treated mice exhibited a marked reduction in MUC5AC expression in the airway compared with the OVA‐induced mice. These reductions were accompanied by reductions in proinflammatory cytokine production and inflammatory cell infiltration. Collectively, these findings indicate that melatonin effectively inhibits MUC5AC expression. These effects may be closely associated with the inhibition of MAPK phosphorylation. Furthermore, our study suggests that melatonin could represent a potential therapeutic for chronic airway diseases, such as asthma and COPD.